QLfANTITAIVE ECOLOGY OF PHYTOPLANKTON IN THE COCHIN BACKWATER - Gopinathan, C P; Nair, P V Ramachandran; Nair, A K Kesavan (Indian Journal of Fisheries, 2011)
A one-year study on the standing crop in terms of chlorophylls, primaryproduction and total-cell counts of four station grids has shown that there wereregional and seasonal variations in the magnitude of phytoplankton production inthe Cochin backwater. Statistically treated using a microcomputor, a multipleregression relationship has been established between parameters within stations.But th